Desarrollo cognitivo y estado nutricional : materia de los determinantes sociales de las inequidades en salud (2009)
ABSTRACT: Studying undernourishment, out the context of poverty, usually doesn’t explain the consequences on intellectual development, making necessary to understand the social factors related to poverty confounding this association. Social determinants theories studying health inequities are useful to understand this issue. The main purpose of this review is to get a good comprehension of this relationship, researching and selecting authors working in this Issue, which allows us to conclude that nutritional state, cognitive and intellectual development of children should be analyzed involving political, community and family variables to develop policies that could transcend individual state.